Ethnolinguistic data on human origin in Selkup - Kim-Maloney, Alexandra A. (Procedia - Social and Behavioral Sciences)
This paper focuses on interdisciplinary research of an important cultural phenomenon - human origin - based on Selkup language, folklore and culture. Selkups are indigenous peoples of Western Siberia belonging to the Uralic language family and sharing cultural features with their neighbors; for example, Kets, Khanty, Evenks, and Siberian Turks. This research could reveal a significant body of human culture, observe how a language reflects people's cognition, and provide ethnolinguistic data for further comparative studies.